Physical activity maintenance in patients with rheumatoid arthritis: a qualitative study. (March 2014) - Loeppenthin, K; Esbensen, BA; Ostergaard, M; Jennum, P; Thomsen, T; Midtgaard, J
Objective: To describe the experience of physical activity maintenance in patients with rheumatoid arthritis. Design: A qualitative salutogenic-oriented interview study. Setting: A rheumatology outpatient clinic. Subjects: A purposive sample of 16 physically active patients (mean age 50, range 37–67) diagnosed with rheumatoid arthritis on average 21 years previously (range 4–46 years). Methods: In-depth interviews were conducted using a semi-structured interview guide to illuminate how the phenomenon 'physical activity maintenance' was experienced by patients with rheumatoid arthritis. The interviews were analysed using systematic text condensation, inspired by Giorgi's descriptive phenomenological methodology. Results: The analysis revealed three categories: (1) knowing and enjoying the body; (2) responsibility and challenges; (3) autonomy and social belonging. On the basis of these categories, the essential meaning of the phenomenon of physical activity maintenance for patients with rheumatoid arthritis was summarized into 'striving for a transparent body and participation', pointing to experiences of sensations of wellbeing, liberation from restrictions and social participation on equal terms with non-arthritis populations. Conclusion: This study demonstrates that physical activity in patients with rheumatoid arthritis may be understood as a resource to resist disability and to feel and stay healthy while creating and sustaining meaningfulness in life.